Analisis Kekerabatan Tanaman Famili Fabaceae Berdasarkan Karakteristik Morfologi di Kecamatan Jatinangor, Kabupaten Sumedang - Salma Rahmah; Sandy Setiawan (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
Indonesia is a country with very high biodiversity both in flora and fauna groups so that Indonesia is nicknamed the "Megabiodiversity" Country. The flora group has high diversity so that it always provides space for continuous study. This can be continued from the provincial, district to sub-district levels. Like one of the provinces in the western part of Indonesia, namely West Java. This province has a wealth of flora that is spread to every corner, including in one of the areas directly adjacent to West Bandung district, known as Jatinangor District. Jatinangor District is one of the areas in Sumedang Regency which is currently in a transitional period towards urban areas. The transition period is certainly a study that needs to be considered because it will impact on the richness of the flora in the region. One group of plants that still survives and is quite often found in Jatinangor District is the Fabaceae or legume family. Fabaceae is a group of plants that ranks third largest (after Orchidaceae and Asteraceae). This plant belongs to the Angiospermae division or plants that have flowers. This family is interpreted as having around 730 genera and 19,400 species with the largest genus being Astragalus (has more than 2000 species), then Acacia (more than 900 species), then Indigofera (more than 700 species), then Crotalaria (600 species), and finally Mimosas (500 species). Fabaceae itself is grouped into 3 subfamilies, namely Mimosoideae, Caesalpinioideae and Papilionoideae. ), and Soybean (Glycine max L). Soybean is the main crop grown with quite a lot of results and uniform size. In addition, there are differences in habitus, leaf shape, and leaf surface between the three types of plants. The variation in the number of samples also indicates the diversity of plant populations in the Fabaceae family at the study site.